Bulgaria : 2008 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Bulgaria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This 2008 Article IV Consultation discusses that Bulgaria has been hit by the global financial crisis, with clear signs that the country's capital inflows-driven boom has come to an end and that the real economy is slowing down. Executive Directors have commended the Bulgarian authorities for their prudent policies that have built strong balance sheets in the public sector. Directors have also welcomed the authorities' commitment to maintaining prudent fiscal policies, which will provide crucial support for the currency board arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet